Morphological Variation in Arabica Coffee (Coffea arabica L.) Growing in North Sumatra Indonesia - Malau, Sabam; Pandiangan, and Samse (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Genetic variation is important in plant breeding. However, information on the genetic variability of Arabica coffee especially in coffee field of North Sumatra was not yet available.  Magnitude of morphological variation, genotypic variation, phenotypic variation, heritability, genetic advance, genetic correlation, and phenotypic correlation of plant vigors and yield components of 28 genotypes were evaluated using nested design.  This research showed morphological and genetic variations of the genotypes in the field. Based on the research locations as operational taxonomic unit, the genotypes were separated into three clusters. Most of the parameters had low to moderate genotypic variation, while phenotypic variation was moderate to high. Heritability and genetic advance were low, moderate, and high. Several plant vigors and yield components had a positive significant genetic and phenotypic correlation one another, and several had negative ones. Coffee berry borer infestation (CBBI) had a highly significant negative genetic correlation with leaf width (rG = -0.309**), leaf weight (rG = -0.671**), fruit diameter (rG = -0.320**), and bean length (rG = -0.175**). CBBI showed a significant positive genetic correlation with mesocarp pH (rG = 0.134*).  To reduce CBBI, selection for higher leaf weight is better. Selection on lower pH of mesocarp could be considered to decrease CBBI.Keywords: cluster analysis, genetic correlation, genetic heritability, variability